Značilnosti otrok in vpletenost staršev v otrokovo učno dejavnost kot napovedniki učne uspešnosti prvošolcev - Horvat, Martina (Šolsko polje, 2010)
This study explored the role of children's characteristics (gender and general non-verbal intelligence) and their parents' academic involvement (parents' cooperation with the school, mothers' education and stimulation of their child's cognitive development) in predicting the first graders' school achievement. Data was collected from Slovene first graders and their mothers (N=328). The children's teachers (N=87) reported on their school achievement in Slovene, mathematics, and environmental education (EE), and on their parents' cooperation with the school. The mothers provided data regarding their own level of education and the stimulation of their child's cognitive development. The children were assessed individually regarding their non-verbal ability. The two blocks of factors (child characteristics and parental academic involvement) explained, 23%, 9%, 7% and 17% of the variance in children's scores (Slovene, mathematics, EE, and aggregated achievement respectively). The combined child and parental factors showed a significantly higher predictive value than the variance predicted by either of the two factors alone. Non-verbal ability and maternal education were significant single predictors across the academic achievement scores. According to the teachers' ratings of achievement, girls attained higher Slovene scores than boys. The parents' level of cooperation with the school was also predicitve of the first graders' Slovene scores.
Keywords: inteligentnost; učenci; starši; medosebna komunikacija; spoznavne sposobnosti; učna uspešnost